PENGGUNAAN KITAB AL-MIFTAH LIL ‘ULUM DALAM PEMBELAJARAN NAHWU PADA SANTRI PONDOK PESANTREN TARBIYATUT THOLABAH LAMONGAN - Mila Nur Fadhila; Isniyatun Niswah (JURNAL AL-IHDA' : Media Ilmiah Bahasa Arab, 2025)
The study of nahwu (Arabic grammar) serves as a fundamental foundation for understanding classical Islamic texts. This research aims to examine the effectiveness of using the book Al-Miftah lil ‘Ulum as a medium for teaching nahwu at Pondok Pesantren Tarbiyatut Tholabah Lamongan. The study employs a descriptive qualitative approach, with data collected through field observations, interviews, and documentation. Findings indicate that Al-Miftah is systematically structured, presents nahwu material thematically with supportive visuals, and effectively enhances students’ learning motivation and comprehension. The combination of traditional methods such as sorogan and bandongan with contextual learning strategies plays a key role in the success of the learning process. Challenges encountered include students' limited vocabulary and lack of confidence in reading and understanding texts. Therefore, a gradual learning approach and intensive support from teachers are required. This study recommends Al-Miftah as an innovative alternative for teaching nahwu in the pesantren (Islamic boarding school) environment.